The origins of Jewish mysticism - Schäfer, Peter (Mohr Siebeck, 2009)
Ezekiel's vision : the cosmos as temple -- Enoch and his circle : ascent to heaven -- Enoch's companions : from the community to the individual -- Qumran : communion with the angels -- Philo : the ascent of the soul -- The rabbis I : approaching god through exegesis -- The rabbis II : the merkava in context -- The merkavah mystics -- Conclusions